Attitudes and Knowledge of dentists in Pakistan regarding the use of Dental Amalgam as a restorative material - Nayab, Talha; Atif, Muhammad; Ayub, Uzair; Bajwa, Sikandar J.; Khan, Malik A.; Babar, Bilal Z.; Khurshid, Maryam; Fayyaz, Mamman (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the attitudes of Pakistani dentists regarding the safe use of amalgam as a restorative material. Study design and setting: This cross-sectional, was conducted at Women medical and dental College, Pakistan. Methods: This cross- sectional study was conducted amongst the dentist of Pakistan. Survey utilized for this study was adopted and modified from the study conducted by Alkhudhairy F. Descriptive statistics were checked by means of percentages and frequency for all variables. In order to check significant difference among the responses given Chi-square test was applied. Results: From a total of 212 participants, there were 97 (45.8%) males and 115 (54.2%) females. There were 167 participants working in private sector while 45 worked in public sector. Amalgam was most commonly preferred for preparation of small cavities, agreed mutually by both males (45.4%) and females (27%). Majority of the male participants (51.5%) stated being unsure regarding the safety of amalgam, while majority of females (49.5%) reported amalgam unsafe for both dentist and the patients. Composite was the frequently used alternative restorative material by both males (39.2%) and females (51.3%). Conclusions: Though amalgam was the utmost frequently used material used for restoration of posterior teeth. Many study participants had awareness regarding the mercury toxicity but still it was used. However additional sessions can be conducted for reinforcing the safety element regarding the use of amalgam.